3D reconstruction of prior β grains in friction stir–processed Ti–6Al–4V. (21st May 2014) - TILEY, J.S.; SHIVELEY, A.R.; PILCHAK, A.L.; SHADE, P.A.; GROEBER, M.A.
Summary The prior β grain structure and orientations in the central stir zone of friction stir–processed Ti–6Al–4V were reconstructed from measured α phase orientations obtained by three‐dimensional serial sectioning in a dual‐beam focused ion beam scanning electron microscope. The data were processed to obtain the α colony and β grain size distributions in the volume. Several β grains were individually analysed to determine the total number of unique α variants and the respective volume fractions of each. The analysis revealed that some grains experienced overwhelming variant selection (i.e. one variant dominated) whereas other β grains contained a more evenly distributed mixture of all 12 variants.